Effect of Twin Boundary Motion and Dislocation-Twin Interaction on Mechanical Behavior in Fcc Metals - Rezaei Mianroodi, Jaber; Svendsen, Bob (Materials, 2020)
The interplay of interface and bulk dislocation nucleation and glide in determining the motion of twin boundaries, slip-twin interaction, and the mechanical (i.e., stress-strain) behavior of fcc metals is investigated in the current work with the help of molecular dynamics simulations. To this end, simulation cells containing twin boundaries are subject to loading in different directions relative to the twin boundary orientation. In particular, shear loading of the twin boundary results in significantly different behavior than in the other loading cases, and in particular to jerky stress flow. For example, twin boundary shear loading along ⟨ 112 ⟩ results in translational normal twin boundary motion, twinning or detwinning, and net hardening. On the other hand, such loading along ⟨ 110 ⟩ results in oscillatory normal twin boundary motion and no hardening. As shown here, this difference results from the different effect each type of loading has on lattice stacking order perpendicular to the twin boundary, and so on interface partial dislocation nucleation. In both cases, however, the observed stress fluctuation and “jerky flow” is due to fast partial dislocation nucleation and glide on the twin boundary. This is supported by the determination of the velocity and energy barriers to glide for twin boundary partials. In particular, twin boundary partial edge dislocations are significantly faster than corresponding screws as well as their bulk counterparts. In the last part of the work, the effect of variable twin boundary orientation in relation to the loading direction is investigated. In particular, a change away from pure normal loading to the twin plane toward mixed shear-normal loading results in a transition of dominant deformation mechanism from bulk dislocation nucleation/slip, to twin boundary motion.